Symbiotic Vs Commensal Networking: the Case of Textile SMEs in China and Russia - Mikhailitchenko, Andrey; Sadovnikova, Anna (Organizations and Markets in Emerging Economies, 2015)
The purpose of this research is to contribute to the literature addressing the characteristics of small and medium enterprises (SMEs) based on the sample drawn from two emerging economies – China and Russia. The study investigates the intensity and typology of networking activities that SMEs are involved in. The research contributes to the field by empirically investigating, testing, and putting into a unified framework the measurement tools required for identifying symbiotic and commensal types of SMEs’ networking interactions. It also provides an insight into attitudinal, managerial, cultural, and environmental factors that condition these two types of networking and influence SMEs’ willingness to globalize their operations and thus make their networks international. The overriding framework of the study can be stated as developing, validating and testing the symbiotic networking concept relatively to the international business studies. In this way, the study contributes to overcoming the criticism that network theory is not predictive by nature and is not testable.